Peran Disiplin Kerja dalam Memengaruhi Motivasi dan Kepuasan terhadap Kinerja (The Role of Work Discipline in Influencing Motivation and Satisfaction on Performance) - Krisna, Andy Endra; Sungkawati, Endang; SM, Suharto (STIE Malangkucecwara, 2025)
This study investigates the factors influencing employee performance at PT. Indolakto Pandaan, East Java, by examining work motivation and job satisfaction as independent variables and work discipline as a mediating variable. Employing a quantitative research design, data were collected via a survey involving 183 respondents selected through saturated sampling techniques. The questionnaire utilized a five-point Likert scale, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Results reveal that both work motivation and job satisfaction significantly affect work discipline, which in turn mediates their impact on employee performance. Additionally, motivation and satisfaction exert direct effects on performance. Optimizing these factors, motivation, satisfaction, and discipline, can enhance workforce effectiveness. The findings offer valuable practical implications for PT. Indolakto Pandaan and similar organizations in formulating human resource management strategies aimed at improving employee performance.